2018
DOI: 10.1057/s41599-018-0196-3
|View full text |Cite
|
Sign up to set email alerts
|

Unsettling antibiosis: how might interdisciplinary researchers generate a feeling for the microbiome and to what effect?

Abstract: Decades of active public health messaging about the dangers of pathogenic microbes has led to a Western society dominated by an antibiotic worldview; however recent scientific and social interest in the microbiome suggests an emerging counter-current of more probiotic sentiments. Such stirrings are supported by cultural curiosity around the 'hygiene hypothesis', or the idea it is possible to be 'too clean' and a certain amount of microbial exposure is essential for health. These trends resonate with the ways i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 42 publications
0
29
0
Order By: Relevance
“…Other individual studies identified other logics, pertaining to cost and logistics (Collard, 2016), pre-emptive action to reduce hardship (Howell and Kean, 2018), and the still controversial killing for research (Singleton and Lidskog, 2018). Finally, Greenhough et al (2018) posit that killing largely invisible microbes (‘almost animals’; Cole, 2016; see Gibbs, 2020) helps think through the killing of different life forms.…”
Section: Killingmentioning
confidence: 99%
“…Other individual studies identified other logics, pertaining to cost and logistics (Collard, 2016), pre-emptive action to reduce hardship (Howell and Kean, 2018), and the still controversial killing for research (Singleton and Lidskog, 2018). Finally, Greenhough et al (2018) posit that killing largely invisible microbes (‘almost animals’; Cole, 2016; see Gibbs, 2020) helps think through the killing of different life forms.…”
Section: Killingmentioning
confidence: 99%
“…We report on what we learnt in more detail elsewhere (Greenhough et al., ). Here we will briefly reflect on how participating in this project affected our participants’ ideas about antibiotic and probiotic approaches to domestic hygiene.…”
Section: The Potential Of Participatory Microbiome Researchmentioning
confidence: 74%
“…Recent studies have shown the confusion and anxieties associated with managing microbial ecologies in the domestic space, especially in terms of how to maintain a home that is both hygienic and healthy. In particular, the University of Oxford's Good Germs Bad Germs project 3 brought to light how a group of households in the United Kingdom struggled with biopolitical norms in association with cleaning (Greenhough et al 2018;Lorimer et al 2019). The following extract from an interview with a couple, for example, illustrates how the smell of bleach can be interpreted as a sign of cleanliness: (Greenhough et al 2018: 5) However, this observation linking the smell of bleach to cleanliness contrasted with concerns from other households about the detrimental impact that bleaching could have through widescale eradication of a household microbiome:…”
Section: Contemporary Ambivalence and Ambiguities In Managing Microbesmentioning
confidence: 99%